Sabotage in Asymmetric Contests – An Experimental Analysis - Matthias Kräkel; Bernd Irlenbusch; Christine Harbring; Reinhard Selten (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
In a contest players compete for winning a prize by effort and thereby increasing their probability of winning. Contestants, however, could also improve their own relative position by harming the other players. We experimentally analyze contests with heterogeneous agents who may individually sabotage each other. Our results suggest that sabotaging behavior systematically varies with the composition of different types of agents in a contest. Moreover, if the saboteur's identity is revealed sabotage decreases while retaliation motives prevail.
Keywords: C91; C72; J33; J41; 330; Contest; Experiments; Sabotage; Tournament; Wettbewerb; Experiment; Nichtkooperatives Spiel; Theorie; Tournament